Management des compétences nouvelle enjeux stratégique pour la gestion ressources humaines - RAMDANI , Laala; ZAOUI, Asma (Dirassat Journal Economic Issue, 2017)
This article deals with the positioning of skills management in relation to the new challenges of Human Resources Management (HRM), where skills have become a strategic tool which aims to optimize the performance and competitiveness of the company. The challenge here is to demonstrate how the skills management makes it possible to reconcile the skills that the company needs with the skills available in the company’s Human Capital.